CLOTHES ON THE RESERVATION SYSTEM ADMINISTRATION COMPANY BERLY TAILOR - Rifat Maududy; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2005)
The development and progress of science and technology (Science and Technology) is now so rapid, especially in this 21st century which is known as term "Century Millennium" one of which is marked  by the development of science and computer technology. Advances in current computer is a lot of benefits among the community, and its use has expanded from regional scale, urban, national and foreign tourists, where one can connect with each other or interact without being limited by distance, place or location of the target. Computerization also plays a very important role in determining the performance and progress or whether a company, this was due to the speed, accuracy or correctness and completeness  in data processing in which there calculation process and data storage is very good. In other words, computerization can improve the efficiency and effectiveness of any work activities, so that it can be said that today almost no one sector or corporate sector not developed a computer-based data processing.